Stable Perturbations of operators and related topics - Xue, Yifeng (World Scientific Publishing Co. Pte. Ltd, 2012)
This book provides a broad introduction to the generalized inverses, Moore–Penrose inverses, Drazin inverses and T–S outer generalized inverses and their perturbation analyses in the spaces of infinite-dimensional. This subject has many applications in operator theory, operator algebras, global analysis and approximation theory and so on.